Influence of Different Additives on the Interaction of Quinolone Antibiotic Drug with Surfactant: Conductivity and Cloud Point Measurement Study. Issue 2 (8th December 2019) - Rahim, Md. Abdur; Mahbub, Shamim; Islam, Md. Kamrul; Ahsan, Sk. Md. Ali; Rana, Shahed; Rub, Malik Abdul; Khan, Anish; Hoque, Md. Anamul
Abstract: Conductometric and cloud point (CP) measurement studies have been performed to investigate the interaction of tetradecyltrimethylammonium bromide (TTAB) and Triton® X‐100 (TX‐100) with ciprofloxacin hydrochloride (CFH) in different solvents over the temperature range of 295.15–315.15 K. CFH is used for the treatment of various bacterial infections. The observed critical micelle concentration (CMC) values of TTAB were found to be reduced in the presence of electrolytes (Na2 SO4 /Na3 PO4 ), and this reduction proceeds with the elevation of salt concentration. The order of the CMC of TTAB follows the trend: cmc H 2 O  >  cmc Na 3 PO 4 > cmc Na 2 SO 4 . The observed CMC values of TTAB were found to increase with increasing temperature and decrease with increasing concentration of CFH in aqueous medium. The values of Gibbs free energy of micellization ( ∆ G m o ) for the TTAB/TTAB + CFH mixture were found to be negative, implying spontaneous micellization. The estimated CP of TX‐100 decreases with increasing concentration of TX‐100 in aqueous medium. The CP values first decrease with increasing concentration of CFH and then increase at higher concentration of CFH almost in all cases investigated. The values of free energy of clouding were found to be positive in all cases studied implying that phase separation of TX‐100 was nonspontaneous. The other thermodynamic parameters associated with the micellization of TTAB and the phase separation of TX‐100 were estimated and explained.